Recogizing safety and liveness - Alpern, Bowen
A formal characterization for safety properties and liveness properties is given in terms of the structure of the Buchi automaton that specifies the property. The characterizations permit a property to be decomposed into a safety property and a liveness property whose conjunction is the original. The characterizations also give insight into techniques required to prove a large class of safety and liveness properties.